Pedagogia e variação linguística no ENEM: análise de questões da área de linguagens, códigos e suas tecnologias - Oliveira, Vitória Rodrigues de (Universidade Federal de São Carlos, 2021)
This work aimed to analyze qualitatively and quantitatively the booklet of languages, codes, and their technologies present in the National High School Exam (ENEM) between the years 2014 and 2019 identifying and emphasizing which and how many were the questions that discuss linguistic variation, relying especially on the theory of linguistic variation of William Labov. After reaching the initial objective proposed for this research, specific ones were unfolded that sought to define what was the variation addressed in the questions in question, what characterizes them, and what were the elements that allowed classifying each question as being a certain type of linguistic variation. In addition, the research also briefly discusses the impacts and controversies that ENEM has, to justify the motivations that led to the choice of it as the test to be examined for this work. Within the limits of the research, it was concluded that in only two years the number of questions on the theme is significant, while in the other years analyzed the number of questions on the theme is statistically lower.
Pedagogy and linguistic variation in ENEM: analysis of questions in the area of ​​languages, codes and their technologies
Keywords: Variação Linguística; ENEM; Sociolinguística; Linguistic Variation; Sociolinguistic; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM